Another World : Zwölf Bettgeschichten - Fischer, Peter; Neubauer, Susanne (Luzern : Kunstmuseum Luzern, 2002)
Bourgeois, Louise ; Fischl, Eric ; Gober, Robert ; Hatoum, Mona ; Hodler, Ferdinand ; Horn, Rebecca ; Németh, Ilona ; Ono, Yoko ; Reed, David ; Rist, Pipilotti ; Chiharu Shiota ; Signer, Roman ; Wilke, Hannah
biog., bibliog. p. 137-142
Duits & Engels
Another World : Zwölf Bettgeschichten / Twelve Bedroom Stories, Kunstmuseum Luzern, 15. Juni bis 29. September 2002
boek